Analyzing and Comparing DNS Lookup Tools in Python - Pinto, José C. C.; Scheid, Eder J.; Franco, Muriel F.; Granville, Lisandro Z. (Anais da Escola Regional de Redes de Computadores (ERRC); 2023: Anais da XX Escola Regional de Redes de ComputadoresDO - 10.5753/errc.2023.913, 2023)
The performance of Domain Name System (DNS) resolvers is crucial, as the majority of the communication in the Internet starts with a DNS lookup to resolve a domain an IP address to reach the desired content. In this sense, the academia has been devoted to measure and analyze the performance of DNS resolvers using different tools. However, such tools might present different results due to their implementation and affect the measurements. Hence, this paper provides an analysis and comparison of there different DNS lookup tools employed in the literature and discuss the impact of the tool selection.